Cancer-specific immune evasion and substantial heterogeneity within cancer types provide evidence for personalized immunotherapy - Martin Thelen; Kerstin Wennhold; Jonas Lehmann; Maria Garcia-Marquez; Sebastian Klein; Elena Kochen; Philipp Lohneis; Axel Lechner; Svenja Wagener-Ryczek; Patrick Sven Plum; Oscar Velazquez Camacho; David Pfister; et al. (npj Precision Oncology, 2021)
Abstract The immune response against cancer is orchestrated by various parameters and site-dependent specificities have been poorly investigated. In our analyses of ten different cancer types, we describe elevated infiltration by regulatory T cells as the most common feature, while other lymphocyte subsets and also expression of immune-regulatory molecules on tumor-infiltrating lymphocytes showed site-specific variation. Multiparametric analyses of these data identified similarities of renal and liver or lung with head and neck cancer. Co-expression of immune-inhibitory ligands on tumor cells was most frequent in colorectal, lung and ovarian cancer. Genes related to antigen presentation were frequently dysregulated in liver and lung cancer. Expression of co-inhibitory molecules on tumor-infiltrating T cells accumulated in advanced stages while T-cell abundance was related to enhanced expression of genes related to antigen presentation. Our results promote evaluation of cancer-specific or even personalized immunotherapeutic combinations to overcome primary or secondary resistance as major limitation of immune-checkpoint inhibition.